2023
DOI: 10.1039/d2tc04080h
|View full text |Cite
|
Sign up to set email alerts
|

High performance flexible electromagnetic interference shielding material realized using ZnO nanorod decorated polyvinylidene fluoride (PVDF)-MXene composite nanofibers

Abstract: High-efficiency, lightweight, and flexible electromagnetic shielding materials are required to manage electromagnetic radiation pollution. However, preparing shielding materials that possess these features simultaneously is challenging. In this study, we report...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Meanwhile, Wang et al claimed that the conductive composite film of AgNW/MXene/polyurethane exhibited an EMI SE of 27.1 dB with a high transmittance of 82.8 % [ 97 ]. The polyvinylidene fluoride (PVDF)-MXene composite nanofiber, which is decorated by ZnO, was developed as a flexible and stable film with an EMI SE of 61 dB [ 98 ]. Due to the 2D structure of the MXene nanosheet, MXene/polymer nanocomposite films fabricated by vacuum filtration often possess a nacre-like ‘‘brick and mortar’’ with a highly ordered nanostructure of MXene [ [99] , [100] , [101] ].…”
Section: Emi Shielding Functionmentioning
confidence: 99%
“…Meanwhile, Wang et al claimed that the conductive composite film of AgNW/MXene/polyurethane exhibited an EMI SE of 27.1 dB with a high transmittance of 82.8 % [ 97 ]. The polyvinylidene fluoride (PVDF)-MXene composite nanofiber, which is decorated by ZnO, was developed as a flexible and stable film with an EMI SE of 61 dB [ 98 ]. Due to the 2D structure of the MXene nanosheet, MXene/polymer nanocomposite films fabricated by vacuum filtration often possess a nacre-like ‘‘brick and mortar’’ with a highly ordered nanostructure of MXene [ [99] , [100] , [101] ].…”
Section: Emi Shielding Functionmentioning
confidence: 99%
“…The EMI shielding testing revealed that the eight‐layer epoxy laminate displays a great reflection performance over −90 dB at the Ku frequency range. Lee et al 152 demonstrated a ZnO nanorod (NR)‐decorated PVDF‐MXene composite nanofibers for the EMI shielding application. The electrospun PVDF‐MXene composite provided superb flexibility, while MXene encapsulated in PVDF and hydrothermally decorated ZnO NRs around the nanofibers offered multiple internal absorption sites.…”
Section: Electrospun Emi Shielding Dopantsmentioning
confidence: 99%
“…17–20 Since 1950, several microwave shielding materials have been investigated and still search for high performance materials is going on. 21…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] Since 1950, several microwave shielding materials have been investigated and still search for high performance materials is going on. 21 It is known that impedance mismatch between interfaces induced by uniform or simple structures makes electromagnetic wave (EMW) dissipation problematic. The shielding effective (SE) of a material relies on its dielectric strength, magnetic permeability, shield thickness, and radiation frequency.…”
Section: Introductionmentioning
confidence: 99%